Identifikasi Morfologi dan Morfometrik Ordo Anura di Kawasan Taman Nasional Gunung Gede Pangrango, Cibodas, Sukabumi - Nurza, Imam Safir Alwan (Kelompok Peneliti Muda Universitas Negeri Jakarta, 2021)
Mount Gede Pangrango National Park (TNGGP) is a nature reserve area divided into seven zoning areas located in West Java province. In this location, there is a place that is lush and humid, so that this location can be a good habitat for herpetofauna, especially the anura group. The purpose of this research was to identify and determine the morphology and morphometric of amphibians in the order Anura. It is hoped that this information can be used to help inventory and improve its conservation. The research method used was descriptive explorative and Visual Encounter Surveys (VES). The research results obtained three species of frogs from the order Anura, namely Megophrys montana, Hylarana chalconota, and Limnonectes microdiscus. These species of frogs have morphology and morphometric that indicate these species have entered their juvenile or adult period. In the three species of frogs found, two species of frogs entered adult phase and one species of frog in juvenile phase.